1989
DOI: 10.2514/3.23167
|View full text |Cite
|
Sign up to set email alerts
|

Alternative fuel spray behavior

Abstract: The effects of alternative fuels on the combustion characteristics of a liquid fuel spray are examined. Fuel properties are varied and the effects of these variations on the structure (drop histories, temperatures, and species concentrations) of the spray flame are calculated. Also, a comparison is made of the differences in two spray flames fueled by a standard NATO fuel and a proposed alternative fuel. The calculations are performed using a reacting, two-phase, two-dimensional flow code that utilizes a Lagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Finally, numerical support from CFD modelling would be beneficial due to the possibility of doing single parameter variations. 73,74…”
Section: Discussionmentioning
confidence: 99%
“…Finally, numerical support from CFD modelling would be beneficial due to the possibility of doing single parameter variations. 73,74…”
Section: Discussionmentioning
confidence: 99%
“…Each was applied to solution of a lowdensity, viscous gas flow in a converging-diverging nozzle of conical shape that simulated flow in a resistojet. This work demonstrated that the numerically intensive DSMC technique could be applied readily to a low-density nozzle flow, where the flow varied from continuum at the throat to rarefied at Presented as Paper 92-3108 at the AIAA/SAE/ASME/ASEE 28th Joint Propulsion Conference, Nashville, TN, July [6][7][8]1992 the exit plane. Furthermore, the DSMC results were successfully validated by experimental measurements made in the near field of the plume.…”
Section: Introductionmentioning
confidence: 99%